The Influence of Belly Dance on the Second Stage of Labor and the Condition of the Baby - Herlyssa (GoAcademica Research & Publishing, 2023)
One alternative to exercise during pregnancy is to participate in belly dance, which is fun and will increase the confidence of pregnant women. This study aimed to determine the effect of belly dance on the duration of the second stage of labor and the condition of the newborn. The research design is quasi-experimental. The intervention group consisted of pregnant women participating in belly dance at least 4 times. At the same time, the control group is pregnant women who do not participate in belly dance. The sampling technique was quota sampling. The samples of pregnant women with a gestational age of 26 weeks were 30 pregnant women in the intervention group and 30 pregnant women in the control group. The study was conducted at the Kebon Jeruk and Palmerah Health Centers in March – December 2017. The results showed that the characteristics of respondents in the intervention and control groups were almost the same, namely age at risk, high education, not working, and multipara. There was a significant difference in the second stage of labor duration after the Belly dance was performed in the intervention group. There was no significant difference in the baby's weight at birth after the Belly dance was performed in both the intervention and control groups. In addition to belly dance, parity also influences belly dance on the duration of the second stage of labor. It is recommended that the Kebon Jeruk sub-district health center introduce belly dance movements to pregnant women as a variation in pregnancy exercise activities